A New Species of Nezumia (Gadiformes: Macrouridae) from Fieberling Guyot, Eastern North Pacific Ocean - Wilson, Raymond R., Jr. (2001)
A new species of the macrourine genus Nezumia is described from specimens collected from the crest of Fieberling Guyot in the eastern North Pacific Ocean. The new species is distinguishable from all other Nezumia species chiefly on the basis of a high number of pelvic fin rays, a relatively high number of first dorsal fin soft rays, a steep blunt snout lacking scales ventrally, a relatively weak suborbital ridge, and a moderately long, thin barbel. Although possibly endemic to the Baja California Seamount Province, the new species appears to lack close relatives among the other Nezumia species of the eastern North Pacific Ocean. It might have arrived there either from a disjunct Tethyan distribution, thus retaining close relatives among the Atlantic Ocean species of Nezumia, or by way of stepping-stone dispersal from the Indowest Pacific Ocean.